Shifting Multilingualism: Jhumpa Lahiri’s Expansion from (Multilingual) Author to (Self-)Translator / Nihkuv mitmekeelsus: Jhumpa Lahiri kasv (mitmekeelsest) kirjanikust (enese)tõlkijaks - Sandra Vlasta (Methis: Studia Humaniora Estonica, 2023)
Abstract: This article traces Jhumpa Lahiri’s trajectory from writer to (self-)translator from the perspective of multilingualism. I am particularly interested in Lahiri’s transition from English to Italian and her return to English, this time as a translator. Indeed, it was not until she began writing in Italian that she became a translator. At the same time, the new language revealed her former bilingualism (English–Bengali). I analyse how Lahiri positions herself as a multilingual poet/translator and how she is positioned through paratexts.